Mengusut Brand Apple Menjadi Brand Ternama di Indonesia - Tessa Adrian; Didik Winardi; Rauly Sijabat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Apple has successfully transformed into one of the leading technology brands in Indonesia, despite facing the challenges of a highly competitive market and relatively high product prices. Apple has successfully become one of the leading technology brands in Indonesia, despite the relatively high price of its products. This study aims to identify the factors that support Apple's success in building a strong brand image and gaining a dominant position in the Indonesian market. The results show that the marketing strategy is effective. Despite the high prices, Apple managed to create an image as a symbol of social status, which drives loyalty and desire to own Apple products in Indonesia. This research provides insights into how Apple manages its branding and marketing strategies to stay relevant and maintain its market share in Indonesia.